Legal Problems of People Rights in the Traditional Knowledge Protection - Soenyono - (Jurnal Aplikasi Manajemen, 2012)
The main problem in protecting the traditional knowledge is the societal role as traditional knowledge owner that specifically own legal culture the is open for foreigner, the statute existence problem and how ware its movement and how the government promote and protect. In Indonesia, the problem open great opportunities for the biopiracy, the societal right and dignity removal for the traditional knowledge that has been maintained for centuries. The research method is normative in nature with historical, sociological and statute approaches. The legal material sources in the research are the primary legal material and secondary legal material. The primary legal materials are obtained mainly from statute. The secondary legal material obtained from text / literature that contain about basic principles of Intellectual Property Right, the traditional knowledge, research results, legal writings that contain actual issues about communal ownership for the traditional knowledge, in the form of books, articles and journal. Legal problem about societal relation with the traditional knowledge ownership including: the existence susceptibility of intellectual property right from bio piracy, no embodiment legal protection yet in the normative regulation either national or international, no special actions of government in the form of political policy and etc, and the cultural and legal awareness of the society itself.Keywords: Legal problem, knowledge protection